Harnessing the Therapeutic Potential of Extracellular Vesicles for Biomedical Applications Using Multifunctional Magnetic Nanomaterials. Issue 13 (8th February 2022) - Yang, Letao; Patel, Kapil D.; Rathnam, Christopher; Thangam, Ramar; Hou, Yannan; Kang, Heemin; Lee, Ki‐Bum
Abstract: Extracellular vesicles (e.g., exosomes) carrying various biomolecules (e.g., proteins, lipids, and nucleic acids) have rapidly emerged as promising platforms for many biomedical applications. Despite their enormous potential, their heterogeneity in surfaces and sizes, the high complexity of cargo biomolecules, and the inefficient uptake by recipient cells remain critical barriers for their theranostic applications. To address these critical issues, multifunctional nanomaterials, such as magnetic nanomaterials, with their tunable physical, chemical, and biological properties, may play crucial roles in next‐generation extracellular vesicles (EV)‐based disease diagnosis, drug delivery, tissue engineering, and regenerative medicine. As such, one aims to provide cutting‐edge knowledge pertaining to magnetic nanomaterials‐facilitated isolation, detection, and delivery of extracellular vesicles and their associated biomolecules. By engaging the fields of extracellular vesicles and magnetic nanomaterials, it is envisioned that their properties can be effectively combined for optimal outcomes in biomedical applications. Abstract : Extracellular vesicles (EV) have emerged as promising platforms for biomedical applications. However, their source, size, content, and function heterogeneity remain critical barriers for clinical translation. By providing cutting‐edge knowledge pertaining to magnetic nanomaterials‐facilitated isolation, detection, and delivery of EV and their associated biomolecules, this review article aims to engage both fields in dialogue to advance future EV‐based theranostic applications.